2019
DOI: 10.1128/mbio.02621-18
|View full text |Cite
|
Sign up to set email alerts
|

Role for a Filamentous Nuclear Assembly of IFI16, DNA, and Host Factors in Restriction of Herpesviral Infection

Abstract: Mammalian cells exhibit numerous strategies to recognize and contain viral infections. The best-characterized antiviral responses are those that are induced within the cytosol by receptors that activate interferon responses or shut down translation. Antiviral responses also occur in the nucleus, yet these intranuclear innate immune responses are poorly defined at the receptor-proximal level. In this study, we explored the ability of cells to restrict infection by assembling viral DNA into transcriptionally sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 47 publications
1
66
0
Order By: Relevance
“…Recently, the reduction of RNA Pol II recruitment by IFI16 was proposed. IFI16 forms nuclear filamentous structures called a “restrictosome” that appear to signal to progeny viral genomes throughout the infected cell nucleus to cause their epigenetic silencing and reduce expression of the viral genes (Merkl and Knipe, 2019[ 16 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the reduction of RNA Pol II recruitment by IFI16 was proposed. IFI16 forms nuclear filamentous structures called a “restrictosome” that appear to signal to progeny viral genomes throughout the infected cell nucleus to cause their epigenetic silencing and reduce expression of the viral genes (Merkl and Knipe, 2019[ 16 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Merkl and Knipe explained the IFI16 restriction role. As a matter of fact, they reported that IFI16 can recruit the other restriction factors such as the promyelocytic leukemia (PML), Sp100 and ATRX to form nuclear filamentous structures named “restrictosome” which signals in cis and trans to suppress the progeny viral DNA (Merkl and Knipe, 2019[ 16 ]). Although, there are many reports describing an antiviral function of IFI16, there is no evidence of its role in CHIKV infection which is the global threat arbovirus.…”
Section: Introductionmentioning
confidence: 99%
“…IFI16 and cGAS cooperate to sense intracellular DNA and enable the optimal production of cGAMP, which activates the STING-TBK1 pathway and induces the production of type I interferon in human keratinocytes or macrophages [23,24]. IFI16 can detect viral DNA, initiate assembly of the inflammasome and mediate cell pyroptosis upon infection with DNA viruses, such as KSHV, EBV or HSV-1 [44]. IFI16 inhibits HPV18 replication by repressing viral gene expression and replication [45].…”
Section: Discussionmentioning
confidence: 99%
“…Given the similar domain structure, PYHIN1 might be expected to regulate transcription in a manner similar to IFI16. However more is known about how IFI16 suppresses viral transcription, namely by promoting the addition of heterochromatin marks (59,60) or by sequestering Sp1 away from viral promoters (21,24), compared with what is known about how IFI16 might enhance host transcription. On the latter, IFI16 positively affects host transcription by activating p53, and Liao et al (61) showed that the two HIN domains of IFI16 directly interact with p53 and enhance p53-DNA complex formation and transcriptional activation.…”
Section: Discussionmentioning
confidence: 99%